EFFECT OF DIETARY CASSAVA MEAL ON GROWTH OF MUD CRAB, Scylla paramamosain - Ketut Suwirya; Muhamad Marzuqi; I Nyoman Adiasmara Giri (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
It is widely recognized that a major constraint to development of a mud crabaquaculture industry is the availability and formulation nutritionally adequate but relatively low cost diets. Development of artificial diets, which seek to minimize inclusion of expensive feed ingredients such as fish and terrestrial meals, is considered to be a priority for improving the profitability of this emerging industry. Typically, carbohydrates such as starches are relatively cheap and therefore offer opportunity to supply dietary energy at low cost. The study examines the capacity of mud crab, Scylla paramamosain to utilize a range of dietary cassava meal as carbohydrate source. Four levels of cassava meal were used at inclusion levels of 0%, 10%, 20%, and 30% in diets. Mud crabs will readily accept the diet containing relatively high levels of cassava meal. This experiment proved that mud crab which fed 10% dietary cassava meal gains weight more than the one fed diet without dietary cassava meal. The increasing level of cassava meal to more than10% in diet reduced final weight and weight gain. To some extent, mud crab, Scylla paramamosain is capable to use dietary carbohydrate from cassava meal. The finding raises the possibility to include 10% cassava meal in formulation low cost diet for mud crab.